Supply chain and value chain analyses of West Java’s Gedong mango variety for modern markets: Analisis rantai pasok dan rantai nilai varietas mangga gedong Jawa Barat untuk pasar modern - Saptana; Ariningsih, Ening; Saliem, Handewi P.; Ashari; Septanti, Kartika S.; De Faveri, Stefano; Johnson, Peter (Analisis Kebijakan Pertanian, 2025)
The main challenge in the supply and value chains of Gedong and Gedong Gincu mangoes lies in the suboptimal diversity, quantity, quality, and consistency of supply in response to market dynamics and consumer preferences, particularly for modern markets. This study aims to: (1) examine the supply chain of Gedong and Gedong Gincu mangoes; (2) analyze the value chain and marketing margins; and (3) formulate an integrated supply chain management strategy to improve access to modern markets. A case study approach was employed between November 2021 and December 2022, utilizing snowball sampling, which involved farmers, collectors, suppliers, modern retailers, and end consumers. Data analysis was carried out using quantitative methods (farm share, margins, and value added) and qualitative methods (roles, interaction patterns, and coordination among supply chain actors). The research results identified six key actors in the supply chain targeting the modern markets. Modern retailers generated the highest value added, at IDR 18,250/kg for Gedong mangoes and IDR 20,000/kg for Gedong Gincu, with the largest profit margins also captured at the retail level. These findings underscore the importance of integrated supply chain management strategies through farmer−retailer partnerships to improve efficiency, enhance value added, and increase the competitiveness of mango products. Policy implications include strengthening farmer institutions in terms of management, financing, fair contract arrangements, and member participation. The government is expected to play a facilitative and mediating role in fostering mutually beneficial and sustainable business partnerships across the supply chain actors.